Assessment of post-surgical functional outcome in children with anorectal malformation - Patel, Jiwan Lal; Memon, M. Amin; Sharma, Shipra; Verma, Jeewan (International Surgery Journal, 2018)
Background: Anorectal malformations (ARMs) comprise a spectrum of congenital anomalies that continue to present a challenge for paediatric surgeons. Advances in modern surgical techniques and neonatal care have greatly improved survival among ARM patients over the last decades, and early mortality is now unusual in the absence of fatal associated cardiac or chromosomal defects. The aim of this study is to measure the functional outcome of ARM by most recent krickenburg classification. Methods: The present longitudinal study was conducted in Department of paediatric surgery, Dr. BRAM hospital, Raipur, Chhattisgarh during study period February 2016 to September 2017. Those patients who had completed their all stages of surgery for anorectal malformation at-least 6 months back and arriving at outpatient department of paediatric surgery were included. Results: Maximum number of patients were in age group of 3 to 5 years (77.8%) and minimum were 9 to 11 years (3.7%). A 50.6% male and 49.4% female child were included in the study. Maximum number of patients had vestibular fistula (38.27% followed by perineal fistula (24.69%), rectobulbar (18.51%) then rectovaginal (7.4%) and rectoprostatic (7.4%). Minimum patients had pouch colon (2.4%) and cloaca (1.09%). Voluntary bowel movement was present in 50% of rectoprostatic and 66.6% of rectovaginal fistula. Eighty percentage rectobulbar and 83.87% vestibular fistula had voluntary bowel movement. Cloaca and Pouch colon had no voluntary bowel movement. In recto-vaginal fistula 66.6% had soiling, of which 50% had grade 1 and 16.6% had grade 2 soiling. In recto-bulbar fistula 40% cases had soiling, out of which 20% had grade1 and 20% had grade 2. In recto-vaginal fistula cases 33 % had constipation, of which 16.5% had grade 1 and 16.6 % had grade 2. In recto-prostatic fistula 16% had constipation which was grade1. Conclusions: In this study, author showed that functional outcomes comparable to matched peers are achieved in the majority of low ARMs after minimally invasive, individualized perineal procedures and regular surgical follow-up. In high type of ARM soiling is the prominent feature while in intermediate ARM constipation is more common.